Mechanical properties of epoxidized palm oil / epoxy resin blend - Alsagayar, Zyad Salem (2015)
In this paper, a blend of epoxy resin and epoxidized palm oil (EPO) was prepared to investigate its mechanical properties. Epoxy and EPO were mixed for 20 minutes at room temperature before mixed with hardener and followed by curing for 2 hours at 100 °C. Tensile, flexural and impact tests were conducted to characterize the blend. In general, the tensile and flexural properties of epoxy resin/EPO decreased when the amount of EPO increased. However, strain at break, toughness and impact strength was slightly increased when the amount of EPO was increased up to 20%.The mechanical properties were reduced due to the reduction of the cross linking density and effect of plasticizer.